Respect the weeds digital transformation rooted in principled leadership vision and innovation - Pope, Adan K.; Buonfiglio, Peter J. (Authority Publishing, 2021)
A true game-changing book, filled with proven tools to inspire you and provide a clear path to a better future for your organization.